Glutaredoxins employ parallel monothiol–dithiol mechanisms to catalyze thiol–disulfide exchanges with protein disulfides. Issue 5 (14th December 2017) - Ukuwela, Ashwinie A.; Bush, Ashley I.; Wedd, Anthony G.; Xiao, Zhiguang
Abstract : Glutaredoxins were demonstrated to be a family of versatile enzymes capable of catalyzing thiol–disulfide exchange involving GSSG/GSH via different catalytic routes either alone or in parallel. Abstract : Glutaredoxins (Grxs) are a family of glutathione (GSH)-dependent thiol–disulfide oxidoreductases. They feature GSH-binding sites that directly connect the reversible redox chemistry of protein thiols to the abundant cellular nonprotein thiol pool GSSG/GSH. This work studied the pathways for oxidation of protein dithiols P(SH)2 and reduction of protein disulfides P(SS) catalyzed by Homo sapiens HsGrx1 and Escherichia coli EcGrx1. The metal-binding domain HMA4n(SH)2 was chosen as substrate as it contains a solvent-exposed CysCys motif. Quenching of the reactions with excess iodoacetamide followed by protein speciation analysis via ESI-MS allowed interception and characterization of both substrate and enzyme intermediates. The enzymes shuttle between three catalytically-competent forms (Grx(SH)(S − ), Grx(SH)(SSG) and Grx(SS)) and employ conserved parallel monothiol and dithiol mechanisms. Experiments with dithiol and monothiol versions of both Grx enzymes demonstrate which monothiol (plus GSSG or GSH) or dithiol pathways dominate a specific oxidation or reduction reaction. Grxs are shown to be a class of versatile enzymes with diverse catalytic functions that are driven by specific interactions with GSSG/GSH.